2017
DOI: 10.1080/17512549.2017.1354780
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in transitioning to low carbon living for lower income households in Australia

Abstract: In the move towards low carbon living, the challenges faced by lower income groups are often overlooked. Recent rises in electricity costs disproportionate to income make this a more critical issue. Based on findings from focus group discussions with 164 lower income households and 18 stakeholders across 4 different climate zones in Australia, this paper reveals the barriers that lower income households face in improving their residential energy efficiency and in achieving low carbon living. While limited fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…• development and construction that adheres to legislated minimum standards rather than exceeds them (Ding, Aminpour et al 2019)-especially given that minimum standards are not regularly updated to align with international benchmarks (Foong, Mitchell et al 2017;Moore and Holdsworth 2019). This may also reflect a lack of political will at all levels of government to improve the built quality and/or degree of environmental sustainability across government levels (Liu, Judd et al 2017). There is recent movement on this front in Australia; energy efficiency requirements for new builds, as stated in the National Construction Code, have been upgraded (Redman 2022).…”
Section: Dwelling Quality and Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…• development and construction that adheres to legislated minimum standards rather than exceeds them (Ding, Aminpour et al 2019)-especially given that minimum standards are not regularly updated to align with international benchmarks (Foong, Mitchell et al 2017;Moore and Holdsworth 2019). This may also reflect a lack of political will at all levels of government to improve the built quality and/or degree of environmental sustainability across government levels (Liu, Judd et al 2017). There is recent movement on this front in Australia; energy efficiency requirements for new builds, as stated in the National Construction Code, have been upgraded (Redman 2022).…”
Section: Dwelling Quality and Conditionsmentioning
confidence: 99%
“…A number of research studies have shown that it can also result in numerous negative impacts on health and wellbeing, many of which have costs (e.g. for mechanical heating and cooling, or additional health and medical care) that can further entrench poverty (Baker, Lester et al 2019b;Liu, Lagisz et al 2019a).…”
Section: Dwelling Quality and Conditionsmentioning
confidence: 99%
“…Energy poverty-sometimes referred to as fuel poverty or energy insecurity-is broadly understood as the lack of adequate energy services to provide basic needs (Harrison & Popke 2011;Reames 2016). Though energy poverty is difficult to define due to objective and subjective indicators 260 Tozer et al Buildings and Cities DOI: 10.5334/bc.304 (Martini 2021), as well as differences in geographical location (Liu et al 2019), some of the most commonly identified drivers of energy poverty are poor energy efficiency, low incomes, and high energy bills, in addition to political, structural, and situational drivers such as the 2022 'gas crisis' (Boardman 1991;Middlemiss 2022). Energy poverty is measured and identified across scales from the household level-e.g.…”
Section: What Is Energy Poverty?mentioning
confidence: 99%
“…Many other studies also revealed the impact of income on electricity consumption, with differing results. Some of them found a positive relation, some a negative and others found no relation to income at all (Alberini, Gans, & Velez-Lopez, 2011;Arikawa, Cao, & Matsumoto, 2014;Copiello & Gabrielli, 2017;Davis, 1998;Farsi, Filippini, & Pachauri, 2007;Fell, Li, & Paul, 2014;Gupta & Köhlin, 2006;Meier, Jamasb, & Orea, 2012;Liu, Judd, & Santamouris, 2017;Manalo-Macua, 2007;Nesbakken, 1999;Reiss & White, 2001).…”
Section: Economic Capabilitymentioning
confidence: 99%